Strategi Pemasaran Digital dan Manajemen Strategis UMKM Kota Palembang - Kristi Renda Andini; Rafikhein Novia Ayuanti (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Marketing management is a planning process. implementing target market control and acquiring, retaining and growing customers through creating, delivering and communicating superior customer value. The aim of this research is to understand consumer needs and behavior, as well as analyze the market environment, increase consumer awareness and recognition of MSME products or services, increase the ability of MSMEs to compete in the market by developing innovative and effective marketing strategies. As for marketing strategies that can help develop MSME businesses and manage wise financial management, strategies can also be described using a SWOT analysis.